The devil is in the details: sex differences in simple bargaining games - Ana León-Mejía; Luis M. Miller (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2007)
The study of gender differences in social preferences has shown mixed results, preventing economists and other social scientists from drawing definitive conclusions on this topic. Several original investigations and experimental reviews have hypothesized that the main reason of this heterogeneity of results is the myriad of experimental designs used to study gender differences. In this paper we test this hypothesis by making male and female participants to face two different but related experimental games and two different information treatments. Through this 2x2 factorial design, we obtain results in line with some recent papers: women are sensitive to the design and context of the experiment in ways that men are not. In addition, we go further providing a well-grounded account on the importance of the context for female decision-making.
Keywords: C78; C91; 330; Beliefs; economic experiments; empathy; gender differences; social preferences; Entscheidung; Geschlecht; Verhandlungstheorie; Test; Frauen; Kognition